High-strength Portland cement clinker with high magnesium oxide content and preparation method of high-strength Portland cement clinker
By adding barite tailings and molybdenum mud to high-magnesium low-grade limestone and using flux to form active minerals and compounds, the problem of low compressive strength of high-magnesium cement clinker is solved, and the strength performance and firing temperature of clinker are significantly improved.
Patent Information
- Application Number
- CN202411760395.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-04
AI Technical Summary
When using high-magnesium and low-grade limestone to prepare cement clinker, the compressive strength of the clinker is relatively low in 28 days, which affects the quality of cement clinker.
The strength performance of the clinker is improved by adding barite tailings and molybdenum mud to high-magnesium low-grade limestone and using sodium carbonate or sodium bicarbonate as flux.
The compressive strength of silicate cement clinker with high magnesium oxide content was significantly improved for 28 days, and at least 3MPa was increased, while the firing temperature was reduced by 50-100℃.
Smart Images

Figure CN119750933A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing silicate cement clinker by utilizing high-magnesium low-grade limestone, and particularly relates to high-strength silicate cement clinker with high magnesium oxide content and a preparation method thereof. Background Art
[0002] High-magnesium low-grade limestone is a kind of interlayer rock with high magnesium content. It is often discarded as waste or sold as aggregate in the cement production process, which not only affects the environment, but also causes waste of mining resources. With the large-scale consumption of high-quality limestone resources by cement manufacturers, in order to reduce production costs and maintain production operations, more and more companies are forced to use high-magnesium low-grade limestone to produce cement clinker, resulting in an increase in magnesium oxide in the clinker. Generally, the magnesium oxide content in the clinker exceeds 4%, which is high-magnesium clinker. With the increase of magnesium oxide in the clinker, not only the normal production of the kiln system is affected, but also the strength of the clinker, especially the 28-day compressive strength is generally low, which seriously restricts the quality of cement clinker. Therefore, it is crucial to use high-magnesium limestone to produce high-strength cement clinker with high magnesium oxide content for the utilization of low-grade raw materials.
[0003] Barite tailings are tailings produced during the mining and selection of barium sulfate ores. The main gangue minerals are calcite, quartz, feldspar and hematite, etc., and also contain a certain amount of barium sulfate. Barium sulfate is used in the calcination process of ordinary Portland cement clinker, which has the effect of increasing system output and reducing the calcination temperature.
[0004] Molybdenum mud is the waste residue discharged when ferromolybdenum is smelted in ferromolybdenum plants. After water quenching, it has a black glassy appearance. In addition to a small amount of molybdenum mud being used to burn clay bricks and other building materials, a large amount of molybdenum mud not only occupies a large amount of land for storage, but also pollutes the surrounding environment. Molybdenum mud contains metal elements such as molybdenum, and reasonable use is conducive to the resource utilization of molybdenum mud. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a high-strength Portland cement clinker with a high magnesium oxide content and a preparation method thereof, which solves the problem of low compressive strength of cement clinker prepared by using high-magnesium low-grade limestone, and makes full use of a large amount of stockpiled high-magnesium low-grade limestone resources and rare metal elements such as barium in barite tailings and molybdenum in molybdenum mud, thereby significantly improving the strength, quality and performance of Portland cement clinker.
[0006] The present invention is achieved in that: A high-strength Portland cement clinker with high magnesium oxide content, composed of the following minerals in weight percentage: C3S: 55-65%, C2S: 15-20%, C3A: 5-10%, C4AF: 8-10%, : 2-5%, CaMoO4: 0.1-1%, f-CaO: 0.5-1.5%.
[0007] Preferably, the raw materials of the high-strength Portland cement clinker with high magnesium oxide content include: calcium raw materials, silicon raw materials, aluminum raw materials and iron raw materials, synergists and fluxes.
[0008] Further preferably, the calcium raw material is high-magnesium low-grade limestone; the silicon raw material is sandstone; the aluminum raw material is slag; the iron raw material is iron tailings; the synergist is barite tailings and molybdenum mud; and the flux is sodium carbonate or sodium bicarbonate.
[0009] Preferably, in the high-strength Portland cement clinker with high magnesium oxide content, the lime saturation ratio KH is controlled at 0.85-0.93, the silicon ratio SM is controlled at 0.23-0.29, and the aluminum ratio IM is controlled at 1.2-1.7.
[0010] Preferably, in the high-strength Portland cement clinker with a high magnesium oxide content, the weight percentage of MgO is 4.0-6.0%.
[0011] Further preferably, the high-strength Portland cement clinker with high magnesium oxide content is ground into high-strength Portland cement with high magnesium oxide content by adding an appropriate amount of gypsum, and its 28-day compressive strength is increased by at least 3 MPa compared with the high-magnesium oxide content Portland cement clinker without the addition of synergist and flux.
[0012] Preferably, the sintering temperature of the high-strength Portland cement clinker with high magnesium oxide content is 1350-1400° C., which is 50-100° C. lower than that of ordinary Portland cement clinker.
[0013] The method for preparing the high-strength Portland cement clinker with a high magnesium oxide content comprises the following steps: S1, crushing and homogenizing the calcium raw materials, silicon raw materials, aluminum raw materials and iron raw materials and sending them to the blending warehouse, and crushing the synergist molybdenum mud and barite tailings and sending them to their respective blending warehouses; S2, the raw materials prepared in step S1 are measured according to the set ratio, and the measured raw materials are sent to the raw material mill, and the flux is evenly and stably added to the raw material feeding belt, and is fed into the mill together with the raw materials to prepare the raw material, and the raw material fineness is controlled at 80 microns and the sieve residue is 10-18%; S3, the raw meal discharged from the mill is sent to the raw meal storage for homogenization; S4, the raw material after homogenization is preheated and then calcined, the outlet temperature of the decomposition furnace is controlled not higher than 850°C, the apparent decomposition rate is controlled to be greater than 90%, the hot raw material after decomposition is put into the kiln for calcination, and the firing temperature is controlled at 1350-1400°C; S5. The clinker discharged from the kiln enters the grate cooler for rapid cooling to obtain high-strength Portland cement clinker with high magnesium oxide content.
[0014] Preferably, in step S2, the raw material fineness is controlled at 10-12% on an 80 micron sieve.
[0015] The main idea of the mineral composition design of the high-strength Portland cement clinker with high magnesium oxide content of the present invention is as follows: The magnesium oxide in the clinker is used to increase the liquid phase volume of the clinker, molybdenum mud is used to improve the calcinability of the clinker, the barium element in the barite tailings is used to form active compounds with calcium, magnesium and silicon elements to improve the compressive strength of the clinker, and the flux sodium carbonate or sodium bicarbonate is added to accelerate the combination of barium with calcium, magnesium and silicon elements.
[0016] The inventors have conducted a large number of experimental studies, and the results show that when the weight percentage of magnesium oxide in the clinker is 4.0-6.0%, 2-3% of the magnesium oxide melts into the clinker minerals, and the remaining magnesium oxide forms There are magnesium compounds such as magnesium oxide, and some magnesium oxide exists in free form. The activity of combined magnesium oxide and free magnesium oxide is very low. Therefore, the strength performance of cement clinker generally decreases with the increase of magnesium oxide content.
[0017] In order to improve the strength of high magnesium oxide content silicate cement clinker, barium ions are introduced into the mixture by using barite tailings to form a hydrated cement clinker with certain hydration activity in the calcination range of 1350-1400℃. Minerals (see formula 1) reduce the free magnesium oxide content, and barium can stimulate the activity of tricalcium silicate in the clinker, thereby significantly improving the strength performance of the clinker. The mineral is a low-temperature mineral and will decompose when the temperature exceeds 1400℃. In addition, the barium element has no mineralization effect. There is still 4-5% free calcium oxide in the clinker within the calcination range of 1350-1400℃. Therefore, measures need to be taken to accelerate the formation rate of cement clinker minerals under low temperature conditions.
[0018] (Formula 1) After a large number of tests and screening, the inventors found that the trace molybdenum element brought into the molybdenum mud can promote the absorption of free calcium oxide by dicalcium silicate in the clinker at a calcination range of about 1400°C, and the clinker can be calcined at low temperature. Retained in the clinker minerals, the above effects further improve the strength properties of the clinker.
[0019] In order to promote the effects of molybdenum and barium, the inventors introduced flux sodium carbonate or sodium bicarbonate to form a liquid phase under a lower calcination temperature of 1350°C, ensuring faster migration of trace elements such as molybdenum and barium in the liquid phase, accelerating the combination of barium with calcium, magnesium and silicon, and ensuring that silicate clinker with a high magnesium oxide content obtains higher strength properties.
[0020] In the preparation method provided by the present invention, the raw material fineness is controlled to be 10-18% on an 80-micron sieve, preferably 10-12%, to ensure that the components of various raw materials are more evenly distributed in the raw material, the clinker mineral reaction is more complete, and the clinker performance is more guaranteed.
[0021] The flux sodium carbonate or sodium bicarbonate is evenly and stably added to the raw material feeding belt, and is fed into the mill together with the raw materials to prepare the raw material. Since the amount of flux used is small, the loss during long-distance transportation can be avoided.
[0022] The advantages and positive effects of the present invention are: (1) The present invention proposes for the first time that, during the sintering process of high-magnesium-content silicate cement clinker, the effect of barium element forming active minerals, the mineralization effect of molybdenum element promoting the absorption of free calcium under low temperature conditions, and the effect of flux providing a low-temperature liquid phase environment to accelerate chemical reactions are coupled to significantly improve the strength properties of high-magnesium-content silicate clinker.
[0023] (2) The method for preparing high-strength Portland cement clinker with high magnesium oxide content of the present invention can ensure that the raw materials are uniformly mixed and the clinker is fired at a relatively low temperature of 1350-1400°C.
[0024] (3) The implementation of the present invention can make large-scale use of high-magnesium low-grade limestone, barite tailings and molybdenum mud, significantly improving the comprehensive utilization rate of resources and the resource utilization rate of waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the diffraction pattern of high-strength Portland cement clinker with high magnesium oxide content provided by Example 3 of the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0027] Embodiment 1~5 The embodiment of the present invention provides a method for preparing high-strength Portland cement clinker with high magnesium oxide content, comprising the following steps: S1, crushing and homogenizing the calcium raw materials, silicon raw materials, aluminum raw materials and iron raw materials and sending them to the blending warehouse, and crushing the synergist molybdenum mud and barite tailings and sending them to their respective blending warehouses; S2, the raw materials prepared in step S1 are measured according to the set ratio, and the measured raw materials are sent to the raw material mill, and the flux is evenly and stably added to the raw material feeding belt, and is fed into the mill together with the raw materials to prepare the raw material, and the raw material fineness is controlled at 80 microns and the sieve residue is 10-18%; S3, the raw meal discharged from the mill is sent to the raw meal storage for homogenization; S4, the raw material after homogenization is preheated and then calcined, the outlet temperature of the decomposition furnace is controlled not higher than 850°C, the apparent decomposition rate is controlled to be greater than 90%, the hot raw material after decomposition is put into the kiln for calcination, and the firing temperature is controlled at 1350-1400°C; S5. The clinker discharged from the kiln enters the grate cooler for rapid cooling to obtain high-strength Portland cement clinker with high magnesium oxide content.
[0028] The raw materials of high-strength silicate cement clinker with high magnesium oxide content include: calcium raw materials, silicon raw materials, aluminum raw materials, iron raw materials, synergists and flux. The calcium raw materials are high-magnesium low-grade limestone; the silicon raw materials are sandstone; the aluminum raw materials are slag; the iron raw materials are iron tailings; the synergists are molybdenum mud and barite tailings; and the flux is sodium carbonate or sodium bicarbonate.
[0029] Examples 1 to 5 By adjusting the amounts of calcium raw materials, silicon raw materials, aluminum raw materials, iron raw materials, synergists and fluxes, high-magnesium silicate cement clinkers with different mineral compositions were obtained.
[0030] Comparative Examples 1 to 3 In the raw material formulation of Comparative Example 1, except that no synergist and flux are added, the amounts of other raw materials are the same as those of Example 3.
[0031] In the raw material formulation of Comparative Example 2, except that molybdenum mud and flux are not added, the amounts of other raw materials are the same as those of Example 3.
[0032] Except for not adding flux, the amounts of other raw materials in the raw material formulation of Comparative Example 3 are the same as those in Example 3.
[0033] The above-mentioned Examples 1 to 5 and Comparative Examples 1 to 3 were analyzed by calculation and diffraction to obtain different mineral compositions in the clinker.
[0034] The diffraction pattern of the high-strength Portland cement clinker with high magnesium oxide content in Example 3 is as follows: Figure 1 As shown; the strength properties of clinker are tested according to the national standard GB / T21372-2008 "Portland cement clinker".
[0035] The raw material fineness, firing temperature, clinker mineral composition, magnesium oxide, free magnesium oxide, free calcium oxide content in the clinker and 28-day compressive strength of the examples 1-5 of the present invention and the comparative examples 1-3 are specifically shown in Table 1.
[0036] Table 1 Data of Examples 1-5 and Comparative Examples 1-3
[0037] The data in Table 1 show that compared with Comparative Examples 1 to 3, Examples 1 to 5 of the present invention introduce molybdenum mud and barite tailings as synergists and sodium carbonate or sodium bicarbonate as fluxes into the raw materials to convert Ca3Mg(SiO4)2 in the clinker into , the free calcium oxide content decreases, and no free magnesium oxide appears. In addition to forming magnesium-containing minerals, the rest of the magnesium oxide is all dissolved in the clinker minerals, thereby obtaining a high-strength silicate cement clinker with a high magnesium oxide content, and its 28-day compressive strength is at least 3MPa higher than that of comparative examples 1 to 3.
[0038] The results of Comparative Examples 1 to 3 show that, based on Comparative Example 1, Comparative Example 2 was calcined at 1375°C due to the addition of barite tailings. Although the free calcium content was high, a small amount of Minerals make the 28-day compressive strength maintain the same strength as the clinker of Example 1 fired at 1450°C. Comparative Example 3 further adds molybdenum mud. Under the promotion of molybdenum element, the free calcium content in the clinker is further reduced and the strength of the clinker is improved.
[0039] The data of Example 3 compared with Comparative Example 3 show that after adding molybdenum mud and barite tailings as synergists, further adding sodium carbonate or sodium bicarbonate as a flux provides more reaction liquid phase, and the free calcium oxide in the clinker is further reduced, which accelerates the sintering rate of the clinker under low-temperature calcination conditions (1350°C). At the same time, the solid solution amount of free magnesium oxide in the liquid phase is increased, rather than existing in a free form, which is beneficial to the improvement of the strength of the clinker.
[0040] The results of the above embodiments and comparative examples show that the high-strength Portland cement clinker with high magnesium oxide content and its preparation method proposed in the present invention can reduce the clinker burning temperature by 50-100°C by introducing barite tailings and molybdenum mud and compounding sodium carbonate or sodium bicarbonate, and form barium- and molybdenum-containing compounds when the MgO content in the clinker is 4-6%, which significantly improves the compressive strength of the high-magnesium Portland cement clinker at all ages, and the 28-day compressive strength is increased by at least 3MPa.
[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents, and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-strength Portland cement clinker with a high magnesium oxide content, characterized in that: Composed of the following minerals in weight percentage: C3S: 55-65%, C2S: 15-20%, C3A: 5-10%, C4AF: 8-10%, : 2-5%, CaMoO4: 0.1-1%, f-CaO: 0.5-1.5%.
2. The high-strength Portland cement clinker with high magnesium oxide content according to claim 1, characterized in that: The raw materials of the high-strength silicate cement clinker with high magnesium oxide content include: calcium raw materials, silicon raw materials, aluminum raw materials, iron raw materials, synergists and fluxes.
3. The high-strength Portland cement clinker with high magnesium oxide content according to claim 2, characterized in that: The calcium raw material is high-magnesium low-grade limestone; the silicon raw material is sandstone; the aluminum raw material is slag; the iron raw material is iron tailings; the synergist is barite tailings and molybdenum mud; and the flux is sodium carbonate or sodium bicarbonate.
4. The high-strength Portland cement clinker with high magnesium oxide content according to claim 1, characterized in that: In the high-strength Portland cement clinker with high magnesium oxide content, the lime saturation ratio KH is controlled at 0.85-0.93, the silicon ratio SM is controlled at 0.23-0.29, and the aluminum ratio IM is controlled at 1.2-1.
7.
5. The high-strength Portland cement clinker with high magnesium oxide content according to claim 1, characterized in that: In the high-strength Portland cement clinker with high magnesium oxide content, the weight percentage of MgO is 4.0-6.0%.
6. The high-strength Portland cement clinker with high magnesium oxide content according to claim 1, characterized in that: The high-strength silicate cement clinker with high magnesium oxide content is ground into high-strength silicate cement with high magnesium oxide content by adding appropriate amount of gypsum, and its 28-day compressive strength is increased by at least 3MPa compared with the high-magnesium oxide content silicate cement clinker without synergist and flux.
7. The high-strength Portland cement clinker with high magnesium oxide content according to claim 1, characterized in that: The sintering temperature of the high-strength silicate cement clinker with high magnesium oxide content is 1350-1400°C.
8. A method for preparing high-strength Portland cement clinker with high magnesium oxide content according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, crushing and homogenizing the calcium raw materials, silicon raw materials, aluminum raw materials and iron raw materials and sending them to the blending warehouse, and crushing the synergist molybdenum mud and barite tailings and sending them to their respective blending warehouses; S2, the raw materials prepared in step S1 are measured according to the set ratio, and the measured raw materials are sent to the raw material mill, and the flux is evenly and stably added to the raw material feeding belt, and is fed into the mill together with the raw materials to prepare the raw material, and the raw material fineness is controlled at 80 microns and the sieve residue is 10-18%; S3, the raw meal discharged from the mill is sent to the raw meal storage for homogenization; S4, the raw material after homogenization is preheated and then calcined, the outlet temperature of the decomposition furnace is controlled not higher than 850°C, the apparent decomposition rate is controlled to be greater than 90%, the hot raw material after decomposition is put into the kiln for calcination, and the firing temperature is controlled at 1350-1400°C; S5. The clinker discharged from the kiln enters the grate cooler for rapid cooling to obtain high-strength Portland cement clinker with high magnesium oxide content.
9. The method for preparing high-strength Portland cement clinker with high magnesium oxide content according to claim 8, characterized in that: In step S2, the raw material fineness is controlled at 10-12% on an 80 micron sieve.